The significant role of entrepreneurial orientation in fostering technological innovation capabilities among small and medium-sized manufacturing enterprises - Mohd Noor, Nor Azila; Muhammad, Azli; Aljanabi, Abdul Qadir Ahmed; Ku Ishak, Awanis (2017)
Technological innovation capabilities have become an important component for small and medium enterprises (SMEs) in the manufacturing industrial sector to cope with intense competition and to fulfill the increasing customers’ requirements and needs. In the midst of such environment, successful manufacturing firms are those wh0 are able to satisfy customers’ needs optimally and not those whose determination is confined to the market’s needs.To achieve such a feat, technological innovation is considered as a suitable mean.Hence, the general consensus is that ‘innovation is power’ for the firms to gain competitive advantage.However, small and medium-sized enterprises (SMEs) in manufacturing sector in particular face tremendous challenges in their attempt to pursue technological innovations. The purpose of this study is to shed further light on the factor influencing technological innovation capabilities among small and medium-sized enterprises manufacturing firms.This study involves a survey among small and medium sized manufacturing firms in Malaysia.In order to effectively generalize the research findings, 112 questionnaires were gathered from the selected respondents.The results show that technological innovation capabilities are positively influenced by entrepreneurial orientation of the firms.The result indicates that strategic orientation that is risk-taking, pro-activeness and innovativeness urges the firms to consider new ideas and take part in creative venture, tolerate risks and proactive.In making decisions that are related to technological innovation, enterprises are likely to consider whether or not they receive entrepreneurial opportunities.The outcome of this study is expected to stimulate future conceptual and empirical research on this important topic and has implications for SME manufacturing managers and policymakers